Analysis of Production and Income Efficiency of Pepper In Landono Sub-District, Konawe Selatan District (Case Study: Endanga Village) - Tamburaka, Irmawatty Paula; Ahmad, Ahmad; Munandar, Hardiyanti (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2020)
This study aims to determine and analyze the price efficiency of pepper farming and analyze how much pepper farming income. By using the quantitative descriptive research method, the sample selection is done by random sampling (simple random sampling) and determined using the Slovin formula, with a total sample of 44 pepper farmers. The analytical method used to describe the relationship between input and output in the production process is the Cobb-Douglas function, Efficiency Test, and farm analysis. The results showed that: Variables in pepper farming that had a significant effect were land area, fertilizer, labor, and farming time variables, while variables that were not significant in pepper farming were seeds and pesticides. This is caused because the use of seeds and pesticides is less than the standard of use. The results of this calculation indicate that pepper farming is not yet price-efficient, because the price efficiency value is greater than 1, so it is necessary to add certain production inputs to be more efficient. Pepper farming is still profitable, this is shown by the R / C ratio of 5.32, it is said that pepper farming is profitable to be developed, to improve efficiency, farmers should be able to use inputs proportionally.